Single-Cell Gene Expression Analysis of a Human ESC Model of Pancreatic Endocrine Development Reveals Different Paths to β-Cell Differentiation - Maja Borup Kjær Petersen (Stem Cell Reports, 2017)
The production of insulin-producing β cells from human embryonic stem cells (hESCs) in vitro represents a promising strategy for a cell-based therapy for type 1 diabetes mellitus. To explore the cellular heterogeneity and temporal progression of endocrine progenitors and their progeny, we performed single-cell qPCR on more than 500 cells across several stages of in vitro differentiation of hESCs and compared them with human islets. We reveal distinct subpopulations along the endocrine differentiation path and an early lineage bifurcation toward either polyhormonal cells or β-like cells. We uncover several similarities and differences with mouse development and reveal that cells can take multiple paths to the same differentiation state, a principle that could be relevant to other systems. Notably, activation of the key β-cell transcription factor NKX6.1 can be initiated before or after endocrine commitment. The single-cell temporal resolution we provide can be used to improve the production of functional β cells.